Design of segmented CRC‐aided spinal codes for IoT applications. Issue 20 (13th November 2020) - Bian, Hongxiu; Liu, Rongke; Kaushik, Aryan; Hu, Yingmeng; Thompson, John S.
Abstract : Rateless spinal codes can achieve reliable transmission with high throughput performance, which is required by some power‐constrained applications, such as internet of things (IoT). In this study, the cyclic redundancy check (CRC) is divided into segments. We design the segmented CRC‐aided (SCA) spinal codes and propose a novel hybrid decoding algorithm. The decoder can terminate the decoding process earlier when an error decoding is detected in any segment. Moreover, a more targeted symbol transmission strategy after decoding errors occur is provided and we call it as the transmitting redundant symbols for specific segments (RSSS) strategy. The RSSS strategy saves the transmitting symbols by transmitting a variable number of symbols, thus improving the throughput of the system. Furthermore, we design a new tail‐biting structure for SCA‐spinal codes to compensate for the disadvantage of poor error detection ability for short segment CRC bits. The simulation results show that the proposed SCA‐spinal codes can reduce the decoding complexity and improve the throughput of the system. The transmission delay can also be reduced by dividing the information bits and CRC bits into an appropriate number of segments.